SPECIFIC CHARACTERISTICS AND SOCIO-ANTHROPOLOGICAL CONTENT OF CONCEPTS OF CRIME AND PUNISHMENT IN NEW UZBEKISTAN (Scientific journal of the Fergana State University, 2024)
In the article, the specific features, necessity, and actuality of the concepts of crime and punishment in New Uzbekistan were researched, and in this process, its socio-philosophical, moral, spiritual, legal classification and specific features were analyzed.